"Streptomyces avermitilis" mutants defective in methylation of avermectins. - Schulman, M D (1987)
"Streptomyces avermitilis" mutants defective in the methylation of the avermectins have been isolated and characterized. Four mutant strains, CR-1, CR-2, CR-3, and CR-4, were unable to methylate the oxygen at C5 of the macrolide moiety and produced essentially only the avermectin B components. These four strains lack avermectin B2 O-methyltransferase (B2OMT) activity. Two mutant strains were unable to methylate the oleandrose moiety at the oxygens at C3' and C3'' and produced essentially only demethylavermectin components. One of these mutants, strain CR-5 (derived from wild-type "S. avermitilis"), produced demethylavermectin A and B components and possessed normal B2OMT levels. The other mutant, strain CR-6 (derived from strain CR-1, which lacks B2OMT activity), produced only demethylavermectin B components. Reaction of 3"-O-demethylavermectin B2a and S-adenosylmethionine with either cell extracts or purified B2OMT resulted in the methylation of the oxygen at C5 of the macrolide moiety and yielded only 3''-O-demethylavermectin A2a as the product. These experiments indicate that different enzymes are required for methylation of the macrolide (the oxygen at C5) and the oleandrose (oxygen at C3) and that methylation of the oleandrose occurs before attachment to the macrolide ring.